2023
DOI: 10.1038/s42005-023-01162-8
|View full text |Cite
|
Sign up to set email alerts
|

Bloch points and topological dipoles observed by X-ray vector magnetic tomography in a ferromagnetic microstructure

Abstract: Bloch points are small 3D magnetic textures with unit topological charge that require the use of advanced vector imaging techniques for their direct experimental characterization. Here we show results from the reconstruction of the magnetization field $${{{{{\bf{m}}}}}}\left({{{{{\bf{r}}}}}}\right)$$ m r of an elongated permalloy microstructure by X-ray vector magnetic tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…This method has identified various 3D magnetic patterns, such as Bloch point dipoles, triplets, asymmetric and helical vortices, and more, at the chirality shifts of an asymmetric Bloch DW within a Permalloy structure. [43] Numerical simulations have suggested that Bloch points may be involved in the transition region of quasi-2D systems during the reversal of vortex cores. [44] Furthermore, Bloch points are sources and sinks of topological charge in topological transitions, such as the unwinding of skyrmion crystals.…”
Section: Introductionmentioning
confidence: 99%
“…This method has identified various 3D magnetic patterns, such as Bloch point dipoles, triplets, asymmetric and helical vortices, and more, at the chirality shifts of an asymmetric Bloch DW within a Permalloy structure. [43] Numerical simulations have suggested that Bloch points may be involved in the transition region of quasi-2D systems during the reversal of vortex cores. [44] Furthermore, Bloch points are sources and sinks of topological charge in topological transitions, such as the unwinding of skyrmion crystals.…”
Section: Introductionmentioning
confidence: 99%